Pengaruh Penerapan Sistem Akuntansi Berbasis Digital terhadap Efisiensi dan Transparansi Pengelolaan Keuangan UMKM di Kota Langsa - Fathia; Nurliza Lubis (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2025)
This study aims to analyze the influence of digital accounting system implementation on the efficiency and transparency of financial management in MSMEs in Langsa City. A quantitative approach was employed, utilizing a survey method with 100 MSME actors who have adopted or are in the process of adopting digital accounting systems. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 23.The results show that the implementation of digital accounting systems has a positive and significant effect on financial efficiency (β=0.67,p<0.001) and financial transparency (β=0.72,p<0.001). Simultaneously, digital accounting systems also contribute significantly to both variables (F=28.74,p<0.001). These findings confirm that digital accounting systems not only enhance efficiency through reduced time and operational costs but also strengthen transparency in financial reporting.This study supports financial management theory, transparency theory, and technology adoption theory, which assert that the use of digital technology can improve overall financial management. The implications of this study emphasize the importance of training and mentoring programs to accelerate digital transformation in the MSME sector, especially in improving digital literacy and overcoming technological implementation challenges.